Whole genome resequencing of a global collection of Napier grass (Cenchrus purpureus) to explore global population structure and QTL governing yield and feed quality traits - Teshome, Abel; Lire, H.; Higgins, J.; Olango, T.; Habte, Ermias H.; Negawo, Alemayehu T.; Muktar, Meki S.; Assefa, Yilikal; Pereira, J.F.; Azevedo, A.L.S.; Machado, J.C.; Nyamongo, D.; et al. (Oxford University Press, 2025)
Napier grass (Cenchrus purpureus) is a C4 perennial grass species native to Sub-Saharan Africa (SSA) and widely used for feed cattle in the region. In this study, we sequenced the genomes of 450 Napier grass individuals from 18 countries, identifying over 170 million DNA variants (SNPs and Indels). Approximately 1% of these SNPs were informative and used to assess genetic diversity within the collection. Our resequencing study provided valuable insights into the global genetic diversity of Napier grass. Additionally, a genome-wide association study on two independent populations identified multiple quantitative trait loci (QTL) significantly associated with key agronomic traits, including biomass yield, nitrogen and cellulose content. These findings serve as a crucial resource for preserving and understanding Napier grass genetic diversity in the context of climate change. Moreover, they will support genomics-based breeding programs aimed at developing high-yielding and drought-tolerant varieties for forage and biofuel production.